Development of homestay tourism in Tukdah village of Darjeeling district, West Bengal: A study based on the perception of homestay owners and tourists - Suvra Maji,; Krishma ,; Alok Sarkar, (National Geographical Journal of India, 2025)
Tourism plays a crucial role in the economic development of many countries and regions by generating employment and enhancing local livelihoods. In India, rural and community-based tourism initiatives have gained attention as sustainable alternatives to mass tourism, particularly in ecologically sensitive hilly regions such as Darjeeling. The present study examines the socio-economic impact of homestay tourism in the vicinity of Lamahatta Eco-Park in the Darjeeling Hills. Homestay tourism has emerged as a viable livelihood option for rural communities by promoting local culture, environmental conservation, and women's empowerment. The paper highlights that homestay-based tourism in Darjeeling provides supplementary income opportunities, encourages community participation, and supports sustainable tourism development. However, challenges such as inadequate infrastructure, lack of training, and limited promotional initiatives constrain its full potential. Understanding these dynamics is essential for policymakers, tourism planners, and local stakeholders to enhance sustainable rural livelihoods and balance economic growth with ecological preservation in the Darjeeling Hills.